Phytochemical screening and antioxidant activity of Brasicca oleracea vegetables from Cikajang, Garut - Mariani, Ria; Rizkio Syamsudin, R. Aldizal Mahendra; Sumarni, Neneng; Wibowo, Diki P (Institute of Computer Science (IOCS), 2023)
Antioxidants from dietary plants have been thought to be good for human health. Brassica oleracea vegetables are potential antioxidant vegetables. Cikajang is one of the vegetable-producing centers in West Java, located in Garut district. Vegetables cultivated in the Cikajang area include cabbage, cauliflower, and keciwis, which are species of Brassica oleracea. There is no research regarding the phytochemistry and antioxidant activity of Brassica oleracea vegetables collected in Cikajang. Behalf of that, this research aims to determine the phytochemical screening and antioxidant activity of cabbage, cauliflower, and keciwis from Cikajang. The phytochemical screening was carried out using several identification reagents, while the antioxidant activity test was carried out using the DPPH (2,2 diphenyl-1-picrylhidrazyl) method. The results of phytochemical screening show that in the dry powder and extract of cabbage, flavonoids, phenols, and steroids/triterpenoids were identified. In the dry powder and extract of cauliflower, flavonoids, saponins, phenols, and steroid/triterpenoids were identified. In the dry powder and extract of keciwis, flavonoids, saponins, gallic tannins, and phenols were identified. The results of the antioxidant activity test using DPPH show that vitamin C as a standard had an IC50 value of 5.223 µg/ml, while the IC50 values of cabbage, cauliflower, and keciwis extracts were 39.948, 35.199, and 15.032 µg/ml, respectively.